Efficient phenothiazine-ruthenium sensitizers with high open-circuit voltage (Voc) for high performance dye-sensitized solar cells. (September 2020) - Jia, Hai-Lang; Li, Shan-Shan; Peng, Zhi-Jie; Zhao, Jiao; Gong, Bing-Quan; Guan, Ming-Yun; Zheng, He-Gen; Xia, Fei-Fei
Abstract: Herein, we designed and synthesized two highly effective phenothiazine-ruthenium sensitizers JR1 and JR2 to use in dye-sensitized solar cells. The structure of N719 was further optimized, 1, 10-phenanthroline modified by phenothiazine was used instead of 2, 2′-bipyridine-4, 4′-dicarboxylic acid to as the electron donor. Compared with N719, these two ruthenium dyes show better optical properties, both the spectral response range and the molar absorption coefficient of dye molecules have been significantly improved. The IPCE response of JR1 is obviously improved, the response range of photocurrent is widened to 800 nm, the overall response value is also higher. JR2 shows the widest and highest IPCE response curve, in the region of 410–600 nm, the IPCE value of JR2 is more than 70%, and at 530 nm, the IPCE value has reached 79%, so JR2 shows the highest Jsc of 17.18 mA cm −2 . Further optimization of molecular structure not only improves the light-harvesting performance of the device, but also reduces the charge recombination behaviour and improves the electron lifetime, so the Voc is greatly increased. Especially for JR2, the introduction of the second long carbon chain not only increases the solubility of the dye, but also further suppresses the dye aggregation and reduces the charge recombination. The phenothiazine-ruthenium dye JR2 shows a high Voc of 841 mV, while the theoretical Voc of DSSCs based on I − /I3 − electrolyte is about 900 mV. JR2 exhibits a superior PCE of 9.12%, which exceeds N719 (8.03%) about 14%. Graphical abstract: Image 1 Without co-sensitization and co-adsorption, the phenothiazine-ruthenium dye JR2 exhibits a superior PCE of 9.12% with a high Voc of 840 mV based on I − /I3 − electrolyte, which exceeds N719 (8.03%) about 14%. Highlights: Two highly effective phenothiazine-ruthenium sensitizers JR1 and JR2 have been designed, synthesized and used for DSSCs. JR2 shows a high Voc of 841 mV, while the theoretical Voc of DSSCs based on I − /I3 − electrolyte is about 900 mV. JR2 exhibits a superior PCE of 9.12%, which exceeds N719 (8.03%) about 14%.